Evaluation of Right Issue and Optimal Capital Structure (Case Study: PT Lippo Karawaci Tbk) (The Indonesian Journal of Business Administration, 2020)
PT Lippo Karawaci Tbk which was established in 1990, is one of the largest real estate company in Indonesia with diversified business sectors. Having a long history and data, it is easy for PT Lippo Karawaci to calculates the optimal capital structure that fits the current business situation. In July 2019, PT Lippo Karawaci completed its right issue as a financing decision to decrease its debt ratio and to fund the company’s future expansion. This research evaluates that decision and compares it to the optimal capital structure. The cost of capital approach was used to calculate the rates in various levels of debt. The research shows that the right issue has a positive impact on decreasing the prior market value debt to equity ratio which was 233%, however, the company has not reached the suggested optimal capital structure at the 10% level. The recommendation for such problem is to decrease the current debt level or to improve the stock price performance that undervalued at 0.49x price per book value. Keywords: Optimal capital structure, cost of capital approach, right issue, debt restructuring